2019
DOI: 10.1002/pat.4638
|View full text |Cite
|
Sign up to set email alerts
|

Description of complementary actions of mineral and organic additives in thermoplastic polymer composites by Flame Retardancy Index

Abstract: This work visualizes the complementary actions of organic and mineral additives in model thermoplastic polymer composites in terms of Flame Retardancy Index (FRI). Thermal and flame retardancy behaviors of ethylene-vinyl acetate copolymer (EVA) composites containing calcium carbonate (CC) mineral and ammonium polyphosphate (APP) organic additives were studied varying composition of additives in the 80/20 EVA/(xCC + (20 − x)APP) composites with x denoting 0, 5, 10, 15, and 20 wt%. Thermogravimetric analysis (TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…As observed in previous sections, using an additive alone can to a limited extent improve flame-retardant properties of PP. Combination of flame retardants is a strategy to improve further the flame retardancy via synergism between various flame retardants [ 140 , 141 , 142 ]. Moreover, the quantity of the used flame retardant can be reduced in polymer so as to prevent mechanical properties deterioration.…”
Section: Combination Of Flame Retardantsmentioning
confidence: 99%
“…As observed in previous sections, using an additive alone can to a limited extent improve flame-retardant properties of PP. Combination of flame retardants is a strategy to improve further the flame retardancy via synergism between various flame retardants [ 140 , 141 , 142 ]. Moreover, the quantity of the used flame retardant can be reduced in polymer so as to prevent mechanical properties deterioration.…”
Section: Combination Of Flame Retardantsmentioning
confidence: 99%
“…By the use of dimensionless Cure Index [21] and dimensionless Flame Retardancy Index (FRI) [22], it was demonstrated that the quality of cure in epoxy composites ( Poor , Good , or Excellent ) can be correlated to the performance of flame retardancy ( Poor , Good , or Excellent ). The FRI was also powerful in exploring the complementary actions of mineral and organic additives in polymer systems in terms of the peak of HRR (pHRR), the total heat release (THR), and the time to ignition (TTI) of neat polymer and polymer composites [23]. In this work, with the aim of recognizing the future ahead of innovations in flame-retardant epoxy composites, reports on flame-retardant epoxy composites were comprehensively reviewed and then classified as a function of their flame retardancy performance by the use of the FRI criterion.…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate the molecules comprehensively, it is necessary to treat a variety of indicators with different dimensions using mathematical methods or equations. For example, Vahabi et al [ 25 , 26 ] defined a simple universal dimensionless index for the first time, known as the flame retardancy index (FRI), which was useful for the comparative evaluation of the flame retardancy performance of thermoplastic systems regardless of the types of polymers and additives used. Li et al [ 27 ] evaluated molecules’ multi-effect comprehensively via a simplified formula method and standard deviation score method.…”
Section: Introductionmentioning
confidence: 99%